Intellectual property law. - Bently, Lionel, 1964-; Sherman, Brad; Gangjee, Dev; Johnson, Phillip (Phillip Michael) (Oxford University Press, 2022)
'Intellectual Property Law' is the definitive textbook on this subject. It clearly sets out the law in relation to copyright, patents, trade marks, passing off and confidentiality, whilst enlivening the text with illustrations and diagrams.